Volunteer Partisan Movement in Rostov Region During Great Patriotic War - V. P. Trut (Научный диалог, 2024)
This article examines the volunteer partisan movement in the Rostov region during the Great Patriotic War. It analyzes its content, as well as the general and specific regional characteristics. The sources for this study include both published and newly identified archival materials, some of which are introduced into scholarly discourse for the first time. The author substantiates the conclusion that the local steppe landscape and the lack of natural shelters had a profoundly negative impact on the scale and nature of the partisans’ military operations. It is established that partisan units, under local conditions, were small in number and could only conduct localized military operations. Many operated solely as reconnaissance and sabotage groups. The analysis conducted by the author leads to the conclusion that the primary tactical forms of combat employed by local partisans were swift and brief military raids and strikes, sabotage actions, as well as military incursions. The author identifies that one of the significant features of the partisan movement in the Rostov region was the Cossack factor. It is argued that the majority of Don Cossacks did not embark on a path of collaboration and actively participated in the partisan movement.